Factors Affecting the Achievement of Company Goals by Maximising Company Profits through Internal and External Factors - Barera, Bergi Elber Ernesto (PT. LITERASI SAINS NUSANTARA, 2023)
In the current era of globalisation, the development of a company is increasingly sophisticated and rapid. With the increasing number of companies, it will complicate opportunities for companies. In this case the company must innovate to face its competitors. This study aims to examine the factors that influence the achievement of company goals by maximising company profits through internal and external factors. This research is literature research, and the data used is secondary data from various literatures. Qualitative descriptive method is used to assess the data obtained. The results showed that company performance is influenced by external factors, because external factors themselves can be used as opportunities or threats, namely the involvement of government agencies and institutions that facilitate the entire process starting from raw materials, production processes and marketing processes to media devices to improve company performance. This is because the participation of related parties can encourage entrepreneurs to be creative. Thus, business people can make superior and quality products.